Scrutinizing The Effect of Song on Students' English achievement and students' English learning Interest - Sunarti, Sunarti; Halim, Abdul; Rahmawati, Yeni; Romadhoni, Mohammad; Indah Wulansari, Farra; Putri Mudi, Nabila; Hayathi, Nurul; Tamara Idrus, Qonita (International Journal of Language Teaching and Education, 2023)
This study aims to investigate whether the use of songs has a significant effect on improving students' English skills, and investigates whether the use of songs has a significant effect on increasing students' interest in learning English. This research is quantitative research. The research subjects were high school students in grade X. The schools were randomly selected from several schools in Samarinda. There are 118 research samples from 3 schools in Samarinda. Cluster random sampling was applied in each school in determining the sample. Data analysis procedure using descriptive statistics and inferential statistics. The research instrument is an English proficiency test which includes vocabulary, structure and listening tests. And a questionnaire of interest in learning English. The results showed that the use of songs had a significant impact on improving students' English skills and had a significant impact on students' interest in learning English. it can be seen from the post-test results that the mean score for the experimental group is 82.00, and the mean score for the control group is 76.77. And based on the t-test Sig (0.01) is smaller than 0.05 which proved that there is a difference. In the results of the english learning interest in questionnaire, the mean score in the experimental group was 155.16 was higher than the mean in the control group, 135.84 in the post-test results. And Sig (0.00) is less than 0.05, this shows a significant difference in student interest in learning from the two groups.